Analisis Sistem Persaingan Bisnis Kuliner Sirkey Cafe and Resto - Karolus Wulla Rato; Mariance Anonce Pedi; Agustinus Toda Ngongo; Alfonsus Dappa; Markus Umbu Zogara; Alfandi Lende (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2025)
The culinary industry in Indonesia is experiencing rapid growth with the emergence of many new restaurants and cafes, making competition in this sector increasingly tight. Sirkey Cafe and Resto is one of the players in the culinary industry that tries to attract consumers with different concepts and services. This study aims to analyze the competitive system faced by Sirkey Cafe and Resto through an industry analysis approach, competitor identification, and SWOT (Strengths, Weaknesses, Opportunities, and Threats) analysis. The results of the analysis show that Sirkey Cafe and Resto has advantages in terms of unique concepts and service quality, but faces challenges in price and location competition that can affect its competitiveness. Competition comes from local restaurants, premium cafes, to fast food restaurants, each of which offers advantages in terms of price, menu variety, and convenience. Opportunities that can be utilized by Sirkey are the trend of healthy food and the development of delivery services through digital platforms. However, threats such as rising raw material prices and increasingly tight competition need to be faced with a strong differentiation strategy. This study provides insight for Sirkey Cafe and Resto managers to optimize internal strengths, minimize weaknesses, and utilize existing opportunities to maintain competitiveness in the culinary market.